Fluid inclusion and oxygen isotope studies in garnets related to cavuslu Skarn iron mineralization, East Turkey - Altunbey, Mehmet; Kilic, Ayse Didem (Pergamon-Elsevier Science Ltd, 2019)
The cavuslu iron (magnetite) mineralization (225000 tons at 33.55% Fe) is located in the skarn zones between the re-crystallized limestone of the Permo-Triassic Malatya Metamorphic rocks and tonalites of the Upper Cretaceous Polat Granitoid. Two stages of garnets can be identified: light coloured and dark coloured garnets which is related to magnetite mineralizations. Electron microprobe analysis (EMPA) indicate the garnets vary from grossularite-andradite (Gr(22)(.32.23.08) And(43)(.95-45.06) PY21.41-23.58; Fe-poor) to grossularite-andradite (Gr(22)(.3423.25) Andr(45)(,39.46.26) PY23.51-23.63;Fe-rich) in compositions. In addition to garnet, epidote, pyroxene, calcite, quartz and magnetite are observed in the studied contact rocks. The magnetite mineralizations are observed associated with the epidote-garnet and pyroxene skams. The main ore mineral is magnetite; smaller amounts of hematite, limonite, pyrite, marcasite, chalcopyrite, covelline-chalcocine, azurite and malachite are also observed in the studied area. The endoskarns consist of pyroxene-garnet and garnet-epidote, the exoskarns are represented by epidote-garnet. The measurements of the fluid inclusion on two stage garnet samples indicate that the retrograde skarn minerals (garnets related to calcification, silicification and epidote, pyroxene) formed at moderate temperatures and salinity (405-550 degrees C and 14.71 to 20.3 wt% NaCl) in grossularite-andradite (Fe-rich), and low temperature and salinity (170-385 degrees C and 4.78 to 10.24 wt% NaCl) in grossularite-andradite (Fe-poor). The delta O-18(SMOW) and calculated delta O-18(H)2O isotope composition of Fe-rich and Fe-poor garnets (+ 0.5 to + 0.6%o; - 0.4 to - 0.5%0; 5.96-11.62%o) indicate that ore forming fluids are formed by magmatic fluids with meteoric and metamorphic waters mixing during the retrograde alteration.
Keywords: Garnet; Fluid inclusion; Magnetite; Skarn; Turkey